Synthesis of flake-shaped NiO-YSZ particles for high-porosity anode of solid oxide fuel cell - Wu, Y.; Dong, Dehua; Ran, R.; Zeng, Y.; Wang, K.; Zongping, S.; Huanting, W. (Wiley-Blackwell Publishing, Inc., 2011)
A new synthesis method of using dehydration of sugar (sucrose)with concentrated sulfuric acid was developed to synthesizemixed oxide ceramic particles with flaky shape. The anodedisks prepared from flake-shaped NiO–YSZ particles withouta pore-forming additive exhibited uniform dispersion of NiOand YSZ and a high porosity (45.6%), leading to improved cellperformance as compared with an anode prepared from conventionalNiO–YSZ powder in Ni–YSZ/YSZ/LSM single cellsoperated with H2 as the fuel; their maximum power densitieswere 381 and 300 mW·cm 2 at 850°C, respectively.